Effect of Biomass Power Plant Effluent on Arachius hypogaea L. - Nagajyothi, P.C.; Dinakar, N.; Udaykiran, Y.; Suresh, C.; Prasad, T.N.V.K.V.; Damodharam, T. (Asian Journal of Chemistry, 2010)
Groundnut plants were grown in pots for a period of 30 d where the soils were treated with different effluent concentrations (25, 50, 75, 100 %) collected near industrial area. The distribution of metals in the soils and corresponding accumulations in the experimental crop was investigated on different experimental days 10, 15, 20, 25 and 30th day. The metals Cr, Cu, Mn, Fe, Co, Ni, Pb, Cd and Zn in plants and soil samples were analyzed using AAS technique. The pot treated with 50 % effluent has shown an increase of all the metals on 20th day whereas in the plants the metal accumulation has increased with 100 % effluent concentration on 25th day. The study could pave the way to draw attention phytoremidiation.